CHANGING MOBILITY OF FILIPINO PROFESSIONALS IN RESPONSE TO K TO 12 IMPLEMENTATION IN THE PHILIPPINES - Reynaldo B. Inocian; Cecilia Elena P. de los Reyes; Gerome L. Lasala; Genara B. Pacaña; Dominador G. Dawa (European Scientific Journal, ESJ, 2015)
Professional Mobility is considered an intrinsic trait or character of a worker that pushes to make a decision to career change (Kumlai, 2007). This study analyzes the changing professional mobility of working professionals, who take 18 units in Professional Education, to qualify the Licensure Examinations for Teachers (LET) as a requirement in teaching for basic education (RA, 7836). It seeks to answer the following objectives: (1) describe the profile of the respondents in terms of age, sex, personal and alma-mater status, professional degrees earned and professional satisfaction, (2) analyze the factors that affected their decision to take the Diploma in Professional Education (DPE), (3) ascertain their propensity to teach and (4) generate respondents’ expectations to the teaching profession. This study employed a descriptive survey method using a purposive sampling of 133 professionals. A survey questionnaire was used as a primary tool. Young Filipino professionals change their career to teaching due to dissatisfaction attributed by unemployment, underemployment, low salaries, boredom, work suffocation and unfulfilled expectations. The competent salary package of the public school teacher is the number one attraction that led to the changing professional mobility. Working professionals have the potentiality to shine in the teaching profession and become passionate, altruistic, and stable with life-changing outlook for both personal and professional growth. Their propensity to teach provides a modest tolerance, a passion for integrity, a culture of excellence and a resolute stewardship for learning, which are vital indicators for a prospective self-efficacy in teaching.